1995
DOI: 10.1097/00004714-199512000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Response to Fluoxetine in Geriatric Patients With Major Depression

Abstract: No consensus exists regarding whether early response to an antidepressant strongly predicts a good outcome, what is the criterion for early response, or when to measure it. We hypothesized that early response (> or = 20% decrease in HAM-d21) after any of weeks 1, 2, or 3 of fluoxetine treatment of major depression in geriatric outpatients would predict a favorable outcome by week 6 or an earlier endpoint accurately enough for clinical use. We also hypothesized that the week 1, 2, and 3 percent changes in 21-it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 20 publications
0
20
0
1
Order By: Relevance
“…Only one geriatric study (Mulsant et al, 2006) compared different cut offs within the same patient group and found that final remission can be predicted after 4 weeks of treatment, although this study did not present confidence intervals. Koran et al (1995) found that their criterion to predict final remission, at least 20% reduction in week 1, 2 or 3, was not a clinically useful predictor because only 64.4% of their patients were correctly classified with regard to remission. This is in accordance with our findings in week 1, where only 54.5% of patients and in week 3 only 64.1% of patients were correctly classified using at least 20% reduction as cut-off.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Only one geriatric study (Mulsant et al, 2006) compared different cut offs within the same patient group and found that final remission can be predicted after 4 weeks of treatment, although this study did not present confidence intervals. Koran et al (1995) found that their criterion to predict final remission, at least 20% reduction in week 1, 2 or 3, was not a clinically useful predictor because only 64.4% of their patients were correctly classified with regard to remission. This is in accordance with our findings in week 1, where only 54.5% of patients and in week 3 only 64.1% of patients were correctly classified using at least 20% reduction as cut-off.…”
Section: Discussionmentioning
confidence: 91%
“…We are aware of only one other study in elderly patients using data from one RCT (n ¼ 671), but this study compared prediction using only one cut off ( 20% reduction) in week 1, 2 and 3 (Koran et al, 1995). Both other geriatric studies compared data from two RCTs (n ¼ 446; Sackeim et al, 2005) or three RCTs (n ¼ 472; Mulsant et al, 2006) thus improving the power but at the cost of loosing internal validity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that time to remission of patients demonstrating depression of late life is about 2 weeks longer compared with younger patients. 182 On the whole, the results of the larger ALCAR studies support a role for ALCAR in depression even when compared with the results obtained with other antidepressants including fluoxetine (eg, Koran et al 183 ).…”
Section: Evidence For Alcar Efficacy In Depressionmentioning
confidence: 89%
“…3 As a consequence, it may be pertinent to reexamine a commonly quoted recommendation, that an antidepressant trial must last at least 6 weeks before considering a change in treatment. 4 Another reason to reexamine the relation between initial symptom change and outcome is that earlier studies [5][6][7][8] recommended treatment change based on analyses in which the treatment objective was defined as response, i.e., a reduction of at least 50% from pretreatment depression severity. The ultimate treatment goal, however, is remission.…”
mentioning
confidence: 99%